Tinjauan fiqh siyasah maliyah terhadap pengadaan barang atau jasa (studi kasus balai perkeretaapian (btp) bandung) - Inzamliya, Urvia I'tiyani (Maliki Interdisciplinary Journal, 2025)
The aim of this research was to revolutionize the process of procuring goods and knowing the principles of procuring goods or services consistent with the islamic faith. The study USES literature methods that data derived from reading books, magazines and also electronic media. Research indicates that in the economic sector, the procurement of goods and services is an important element of the economy. In the process, there are frequent infractions of some officials. Common examples include corruption, collusion, and nepotism (KKN), which most of the cases handled by KPK, occur in the process of procurement and services or auction. Many people try to achieve their goals in various ways, such as bribery in the tender tender process. These practices are often performed by commitment officials (PPK) and auction committees to accommodate certain interests, resulting in decisions that are favorable to the parties involved. In Islam an auction is allowed as long as it does not break the rules and does not inflict harm or youth, but is warned if it involves elements of usury or harm others